A tale of two bacterial enteropathogens and one multivalent vaccine. (10th July 2019) - Barry, Eileen M.; Levine, Myron M.
Abstract: Shigella and enterotoxigenic Escherichia coli (ETEC) are among the top four enteric pathogens that cause diarrheal illness in young children in developing countries and are major etiologic agents of travellers' diarrhoea. A single vaccine that could target both of these pathogens would have significant public health impact. In this review, we highlight the many pivotal contributions of Phillippe Sansonetti to the identification of molecular mechanisms of pathogenesis of Shigella that paved the way for the development of rationally designed, novel vaccines candidates. The CVD developed a series of live attenuated Shigella vaccine strains based on the most prevalent serotypes associated with disease. Shigella vaccine strains were engineered to express critical ETEC antigens to form a broadly protective Shigella ‐ETEC multivalent vaccine.